Saturation of the MEA solution with CO2: Absorption prototype and experimental technique - Miriam Navarrete Procopio; Gustavo Urquiza; Laura Castro; Victor Zezatti (Results in Engineering, 2023)
The carbon dioxide (CO2) emissions from thermoelectric power plants contribute to global warming. The Monoethanolamine (MEA) solution is the most widely used solvent for CO2 removal processes from these power plants with the disadvantage that it is expensive and corrosive at high concentrations. In this work, an experimental methodology is developed to fix the operating flow ratio (L/G) that ensures the maximum absorption capacity of MEA solution. The absorption system prototype and the experimental saturation technique are detailed. The main parameters of the experimental technique were the amount (0.65 and 1.30 kg) and concentrations (10,15, 20, 25, and 30 wt%) of MEA solution with CO2 inlet gas concentration (12.5 vol%). The experimental technique shows that MEA saturation occurs when the maximum temperature increase in the solution. Continuous tests were developed to operate the absorption system with the maximum absorption capacity of the MEA solution. The results show that the temperature increases in the MEA solution are a function of the flow rates (L/G) and the MEA concentration. Furthermore, the density, viscosity, and refractive index of CO2-free and CO2-saturated MEA solution at concentrations of MEA below 30 wt% are also measured in this work.